Antiapoptotic cytokine IL-3 + SCF + FLT3L influence on proliferation of gamma-irradiated AC133+/CD34+ progenitor cells - Vávrová, J; Vokurková, D; Mareková, M; Bláha, M; Jebavý, L; Filip, S (Folia biologica, 2002)
Recovery from radiation-induced bone marrow aplasia depends on appropriate cytokine support. The aim of our work was to find a cytokine combination allowing in vitro gamma-irradiated (2.5 Gy) CD34+/AC133+ haematopoietic stem cells to evade radiation-induced apoptosis and to enhance damage reparation, which should enable proliferation and ex vivo expansion of cells. Cells were isolated using separation in a Cobe separator followed by immunomagnetic selection by antibody against the AC133 antigen. Thus isolated cells were 80% AC133+/CD34+ and 10% of them expressed the CD33+ antigen. Ten thousand of AC133+ cells formed 1146 CFU-GM and 304 BFU-E. We proved a high expansion efficiency of cytokine combination SCF + IL-3 + FLT3L in comparison with the combination SCF + IL-3 + IL-11 in both, non-irradiated cells and cells irradiated with a dose of 2.5 Gy. The D0 value for AC133+ cells was determined by the clonogeneity test. The D0 value for CFU-GM was estimated to be 1.08 Gy and for BFU-E 0.95 Gy. The results of DNA analysis showed that the majority of isolated AC133+ cells were in G0/G1 phase of the cell cycle. We proved that the dose of 2.5 Gy induced massive apoptosis (80%) of these cells without progression through the cell cycle, which indicates interphase cell death. Under the influence of cytokine combination (SCF + IL-3 + FLT3L), the surviving 20% of cells entered the cell cycle and, similarly to non-irradiated control cells, on 7th day 35% of cells were in S phase.
Keywords: interleukin-3; Membrane Proteins; Cell Division; Humans; Gamma Rays; Cell Cycle; radioprotektivní látky; Radiation-Protective Agents; imunofenotypizace; záření gama; hematopoetické kmenové buňky; lidé; Interleukin-3; Recombinant Proteins; apoptóza; buněčné linie; rekombinantní proteiny; Immunophenotyping; Cell Line; růstový faktor kmenových buněk; membránové proteiny; Hematopoietic Stem Cells; Stem Cell Factor; buněčný cyklus; Apoptosis; buněčné dělení